Emergency transfusion with whole blood versus packed red blood cells: A study of 1400 patients. Issue 4 (10th February 2023) - Ruby, Kristen N.; Dzik, Walter H.; Collins, Julia J.; Eliason, Kent; Makar, Robert S.
Abstract: Background: Low‐titer group O whole blood (LTOWB) is increasingly used for emergency transfusion. We studied whether initial release of LTOWB compared with packed red blood cells (pRBCs) reduced overall blood requirements for patients needing emergency transfusion. Secondary outcomes examined included survival and non‐lethal adverse clinical outcomes. Study Design and Methods: A retrospective, single‐center, before‐versus‐after study compared patients transfused with emergency‐release, uncrossmatched pRBC followed by component therapy (2016–2019) versus patients transfused with emergency‐release, uncrossmatched LTOWB followed by component therapy (2019–2022). Results: Outcomes were available for 602 patients in the pRBC group versus 749 in the whole blood group. The two groups were similar for age, sex, race, estimated blood volume, ABO blood groups, and underlying diagnosis. Use of LTOWB was associated with increased blood product use at 24 h (4.0 (2.0–12.0) in pRBC group versus 6.5 (4.2–12.7) in LTOWB group, p < .0001) and at 7 days (5.5 (3.0–13.0) in pRBC group versus 7.3 (4.3–14.3) in LTOWB group, p < .0001). Initial use of LTOWB was not associated with improved 24 h or 30 day survival nor lower incidence of non‐lethal adverse clinical outcomes compared with pRBC. Discussion: Our study showed a statistically significant increase in total blood use and blood acquisition costs for patients receiving initial emergency transfusion with LTOWB compared with pRBC. The initial use of LTOWB offered no advantage over component therapy for 30 day survival or selected non‐lethal adverse outcomes.